Shifting national surveillance of Shigella infections toward geno‐serotyping by the development of a tailored Luminex assay and NGS workflow - Ventola, Eleonora; Bogaerts, Bert; De Keersmaecker, Sigrid C. J.; Vanneste, Kevin; Roosens, Nancy H. C.; Mattheus, Wesley; Ceyssens, Pieter‐Jan (MicrobiologyOpen (Weinheim), 2019)
The phylogenetically closely related Shigella species and enteroinvasive Escherichia coli (EIEC) are responsible for millions of episodes of bacterial dysenteriae worldwide. Given its distinct epidemiology and public health relevance, only Shigellae are subject to mandatory reporting and follow‐up by public health authorities. However, many clinical laboratories struggle to differentiate non‐EIEC, EIEC, and Shigella in their current workflows, leading to inaccuracies in surveillance and rising numbers of misidentified E. coli samples at the National Reference Centre (NRC). In this paper, we describe two novel tools to enhance Shigella surveillance. First, we developed a low‐cost Luminex‐based multiplex assay combining five genetic markers for species identification with 11 markers for serotype prediction for S. sonnei and S. flexneri isolates. Using a test panel of 254 clinical samples, this assay has a sensitivity of 100% in differentiation of EIEC/Shigella pathotype from non‐EIEC strains, and 68.7% success rate in distinction of Shigella and EIEC. A novel, and particularly successful marker was a Shigella‐specific deletion in the spermidine acetyltransferase gene speG, reflecting its metabolic decay. For Shigella serotype prediction, the multiplex assay scored a sensitivity and specificity of 96.6% and 98.4%, respectively. All discrepancies were analyzed with whole‐genome sequencing and shown to be related to causative mutations (stop codons, indels, and promoter mutations) in glycosyltransferase genes. This observation spurred the development of an in silico workflow which extracts the Shigella serotype from Next‐Generation Sequencing (NGS) data, taking into account gene functionality. Both tools will be implemented in the workflow of the NRC, and will play a major role in the shift from phenotypic to genotyping‐based surveillance of shigellosis in Belgium. We present and validate a hybrid methodology for contemporary surveillance of Shigellosis. This is based on Luminex‐based multiplex assay for rapid identification and typing, and an NGS‐based follow‐up for epidemiological surveillance.